2023
DOI: 10.1111/sms.14509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of movement‐evoked and tonic experimental pain on muscle force production

Hélio V. Cabral,
Valter Devecchi,
Chelsea Oxendale
et al.

Abstract: IntroductionWhen performing an exercise or a functional test, pain that is evoked by movement or muscle contraction could be a stronger stimulus for changing how individuals move compared to tonic pain. We investigated whether the decrease in muscle force production is larger when experimentally‐induced knee pain is directly associated to the torque produced (movement‐evoked) compared to a constant painful stimulation (tonic).MethodsTwenty‐one participants performed three isometric knee extension maximal volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…Briefly, the greater the load of strength work, the greater the shoulder pain, which also negatively affects the perception of accumulated fatigue. A direct association has been observed between increased muscle force production and increased pain intensity ( Cabral et al, 2023 ). Besides, the accumulation of pain can increase the effort sense ( Hollander et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the greater the load of strength work, the greater the shoulder pain, which also negatively affects the perception of accumulated fatigue. A direct association has been observed between increased muscle force production and increased pain intensity ( Cabral et al, 2023 ). Besides, the accumulation of pain can increase the effort sense ( Hollander et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this method is habituation with repeated or constant stimulation [ 25 ], but it appears this can be mitigated in the short term by using low frequency sinusoids [ 21 , 24 , 26 ]. Two recent studies have demonstrated that these low frequency sinusoidal stimulation protocols can induce moderate knee pain along with observable neuromuscular and mechanical adaptions [ 24 , 27 ]. However, these studies were performed in static conditions (standing, seated), so it unknown if these findings extend to dynamic conditions like locomotion.…”
Section: Introductionmentioning
confidence: 99%